Instilling Multicultural Values in History Learning at SMA N 1 Rembang - Lestariningsih, Wahyu Adya; Jayusman, Jayusman; Purnomo, Arif (Indonesian Journal of History Education, 2021)
The purpose of this research is to know what multicultural values are implemented in learning history in SMA Negeri 1 Rembang, to know the implementation of multicultural values in SMA Negeri 1 Rembang, and know what constraints faced in instilling multicultural values in SMA Negeri 1 Rembang. This research type is qualitative research. Data collection techniques are observation, interview, and documentation. Data validity uses triangulation and source techniques. Data analysis uses an interactive analysis model. The research results reveal that planting multicultural values in teaching history taught in SMA Negeri 1 Rembang has been done well. The implementation of multicultural values in history learning in SMA Negeri 1 Rembang is not only taught in the classroom but also through out-of-class learning. The curriculum becomes an obstacle to instilling multicultural values in SMA Negeri 1 Rembang, and classroom learning becomes a supporting factor in implementing multicultural values.